2014
DOI: 10.7453/gahmj.2013.010
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Publications from the Anthroposophic Medicine Outcomes Study (AMOS): A Whole System Evaluation Study

Abstract: Anthroposophic medicine is a physician-provided complementary therapy system that was founded by Rudolf Steiner and Ita Wegman. Anthroposophic therapy includes special medicinal products, artistic therapies, eurythmy movement exercises, and special physical therapies. The Anthroposophic Medicine Outcomes Study (AMOS) was a prospective observational multicenter study of 1631 outpatients starting anthroposophic therapy for anxiety disorders, asthma, attention deficit hyperactivity disorder, depression, low back … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 43 publications
(385 reference statements)
0
29
0
Order By: Relevance
“…(1) RM treatment during the 12 months before enrollment in the study (2) Age < 18 or > 75 (3) Infections with pathogens (4) Fever (5) Furuncles, eczema, and fungi (6) Burns and open wounds. RM was performed by three different RM therapists, who have certification from the School for Rhythmical Massage of the Ita Wegman Hospital (Arlesheim, Switzerland) or from the Swiss EMR (Erfahrungs Medizinisches Register).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) RM treatment during the 12 months before enrollment in the study (2) Age < 18 or > 75 (3) Infections with pathogens (4) Fever (5) Furuncles, eczema, and fungi (6) Burns and open wounds. RM was performed by three different RM therapists, who have certification from the School for Rhythmical Massage of the Ita Wegman Hospital (Arlesheim, Switzerland) or from the Swiss EMR (Erfahrungs Medizinisches Register).…”
Section: Methodsmentioning
confidence: 99%
“…6 This study focused on chronic diseases and revealed that use of AM-including, but not limited to, RM-was associated with symptom reduction and improvement of health-related quality of life (HRQoL) for the following indications: chronic depression 7 ; anxiety disorders 8 ; chronic low-back pain 9 ; attention-deficit hyperactivity disorder (ADHD) 10 ; migraine 11 ; and asthma. 12 When the data from the patients in the Anthroposophic Medicine Outcomes Study, who were treated with RM, were analyzed independently of their diagnoses, long-term reductions of symptoms and improvements in HRQoL were observed.…”
Section: Clinical Outcomes Of Rhythmical Massagementioning
confidence: 99%
“…A Health-Technology Assessment Report and a 2011 update identified 265 clinical studies on the efficacy and effectiveness of anthroposophic medicine. [21][22][23] The integrative treatment approach with anthroposophic medicine seemed helpful in this case, but separating out how the specific therapies contributed to the overall progress is not feasible. Medications play a limited role in treatment of PRS.…”
Section: Discussionmentioning
confidence: 99%
“…The quality and quantity of the scientific underpinnings of AH are growing [15,[19][20][21][22][23]. Recently, in the Netherlands, patient experiences with AH were measured by means of a CQ-Index AH [24].…”
Section: Introductionmentioning
confidence: 99%